Compatible solid polymer electrolyte based on methyl cellulose for energy storage application: structural, electrical, and electrochemical properties - Aziz, Shujahadeen B.; Brevik, Iver; Hamsan, Muhamad H.; Brza, Mohamad A.; Nofal, Muaffaq M.; Abdullah, Aziz M.; Rostam, Sarkawt; Al-Zangana, Shakhawan; Saifful Kamaluddin, Muzakir; Kadir, Mohd F. Z. (MDPI, 2020)
Compatible green polymer electrolytes based on methyl cellulose (MC) were prepared for energy storage electrochemical double-layer capacitor (EDLC) application. X-ray diffraction (XRD) was conducted for structural investigation. The reduction in the intensity of crystalline peaks of MC upon the addition of sodium iodide (NaI) salt discloses the growth of the amorphous area in solid polymer electrolytes (SPEs). Impedance plots show that the uppermost conducting electrolyte had a smaller bulk resistance. The highest attained direct current DC conductivity was 3.01 × 10−3 S/cm for the sample integrated with 50 wt.% of NaI. The dielectric analysis suggests that samples in this study showed non-Debye behavior. The electron transference number was found to be lower than the ion transference number, thus it can be concluded that ions are the primary charge carriers in the MC–NaI system. The addition of a relatively high concentration of salt into the MC matrix changed the ion transfer number from 0.75 to 0.93. From linear sweep voltammetry (LSV), the green polymer electrolyte in this work was actually stable up to 1.7 V. The consequence of the cyclic voltammetry (CV) plot suggests that the nature of charge storage at the electrode–electrolyte interfaces is a non-Faradaic process and specific capacitance is subjective by scan rates. The relatively high capacitance of 94.7 F/g at a sweep rate of 10 mV/s was achieved for EDLC assembly containing a MC–NaI system.